ACTIONS TO IMPROVE THE WELL-BEING OF THE POPULATION AND ENSURE EMPLOYMENT IN RURAL AREAS (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
This article describes ways to ensure the well-being and employment of the population in rural areas.